Qualitative Analysis of Farmers' Perceptions of Deforestation and Climate Change - Mahdalena Mahdalena; Ahmad Rajuli (Journal of Agribusiness and Natural Resources, 2025)
This study aims to qualitatively analyse farmers' perceptions of deforestation and climate change and explore how these perceptions influence the agricultural adaptation strategies they implement. The study was conducted in X District, Y Province, Indonesia, using a qualitative descriptive approach. A total of 20–25 farmers were selected through purposive sampling based on a minimum of 10 years of farming experience. Data were collected through in-depth interviews, participatory observation, and focus group discussions (FGDs), then analysed using thematic analysis with triangulation of sources and member checks to ensure the validity of the findings. The results showed that most farmers were aware of significant changes in the last 10–20 years, particularly erratic rainfall patterns, increased drought, and more frequent extreme weather events. In addition, farmers also identified deforestation, such as illegal logging and conversion of forests to plantations, as factors affecting microclimate change and land productivity. Although the level of scientific understanding of the relationship between deforestation and climate change varies, empirical experience is the main basis for shaping their risk perceptions and adaptive responses. Adaptation strategies implemented include crop diversification, planting schedule adjustments, crop rotation, soil conservation, shelterbelt planting, water management, and manual pest control. Differences in perceptions and adaptations were also found based on age groups, with more experienced farmers tending to have a more holistic understanding and implement more systematic conservation strategies. These findings confirm that risk perception plays an important role in shaping farmers' adaptive capacity. Therefore, climate change adaptation and mitigation policies need to consider local perspectives, strengthen access to information, and increase institutional support to encourage sustainable and climate-resilient agricultural practices.